N-Terminal Region of GbIspH1, Ginkgo biloba IspH Type 1, May Be Involved in the pH-Dependent Regulation of Enzyme Activity - Bok-Kyu Shin; Joong-Hoon Ahn; Jaehong Han (Bioinorganic Chemistry and Applications)
GbIspH1, IspH type 1 in Ginkgo biloba chloroplast, is the Fe/S enzyme catalyzing the reductive dehydroxylation of HMBPP to isopentenyl diphosphate (IPP) and dimethylallyl diphosphate (DMAPP) at the final step of methylerythritol phosphate pathway in chloroplast. Compared to the bacterial IspH, plant IspH, including GbIspH1, has an additional polypeptide chain at the N-terminus. Here, biochemical function of the N-terminal region of GbIspH1 was investigated with the N-terminal truncated GbIspH1 (GbIspH1-truncated). Both wild type GbIspH1 (GbIspH1-full) and GbIspH1-truncated were catalytically active and produced IPP and DMAPP in a ratio of 15 : 1. Kinetic parameters of KM (17.3 ± 1.9 and 14.9 ± 2.3 µM) and kcat (369 ± 10 and 347 ± 12 min−1) at pH 8.0 were obtained for GbIspH1-full and GbIspH1-truncated, respectively. Interestingly, GbIspH1-full and GbIspH1-truncated showed significantly different pH-dependent activities, and the maximum enzyme activities were obtained at pH 8.0 and 7.5, respectively. However, catalytic activation energies (Ea) of GbIspH1-full and GbIspH1-truncated were almost the same with 36.5 ± 1.6 and 35.0 ± 1.9 kJ/mol, respectively. It was suggested that the N-terminal region of GbIspH1 is involved in the pH-dependent regulation of enzyme activity during photosynthesis.